2017
DOI: 10.14196/mjiri.31.39
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of teriparatide compared with alendronate and risedronate for the treatment of postmenopausal osteoporosis patients in Iran

Abstract: Background: Hip, vertebral and wrist fractures are the most common consequences of osteoporosis. This study aimed at analyzing the cost-effectiveness of teriparatide (CinnoPar®), compared with alendronate and risedronate, in the treatment of women aged 60 and over with postmenopausal osteoporosis in Iran. Methods: A decision tree model with a 2-year time horizon was used to compare treatment with teriparatide (CinnoPar®) with the following treatment strategies: two years of treatment with alendronate and two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…A Markov model was used in 21 studies, consisting of a Markov cohort model ( n = 12) or a Markov microsimulation model ( n = 9). One study applied a discrete-event simulation model [ 16 ], another a decision-tree model [ 13 ]. Quality-adjusted life-years (QALYs) were used as the outcome in these 23 studies with a model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Markov model was used in 21 studies, consisting of a Markov cohort model ( n = 12) or a Markov microsimulation model ( n = 9). One study applied a discrete-event simulation model [ 16 ], another a decision-tree model [ 13 ]. Quality-adjusted life-years (QALYs) were used as the outcome in these 23 studies with a model.…”
Section: Resultsmentioning
confidence: 99%
“…Given the WTP threshold of US$20,000), raloxifene was not cost effective Karnon et al [ 14 ] Women with a mean age of 72 years (range 60–90 years) with a mean BMD T-score at the femoral neck of − 2.15, and with 24% of women having experienced a previous fracture Patented denosumab vs generic alendronate 2012 Deterministic probabilistic Compared with alendronate, denosumab had an ICER of AUD$246,749 per QALY gained. Given the WTP threshold (AUD$100,000), denosumab is not cost effective Azar et al [ 13 ] Postmenopausal women aged over 60 years with BMD T-score ≤ 2.5 and with at least a previous spine, wrist, or hip fracture caused by osteoporosis Risedronate vs (alendronate and teriparatide) 2014 One-way Compared with risedronate, alendronate and teriparatide had ICERs of US$-2178 and US$483,783 per QALY gained. Given the WTP threshold (US$14,010), alendronate is the dominant and cost-effective treatment option.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, it is alleged that electroacupuncture is a more cost-effective intervention that NSAIDs in treatment of patients with chronic low back pain from perspective of society [ 33 ]. For osteoporosis, teriparatide is not a cost-effective intervention compared to alendronate and risedronate from health system perspective in the treatment of postmenopausal Iranian women aged 60 years and above [ 34 ]. Rituximab versus disease-modifying anti rheumatoid drugs (DMARDs) is not a cost-effective intervention for the treatment of patients with refractory rheumatoid arthritis from health service perspective [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…These patients were provided with additional information to increase their knowledge and possible side effects were addressed and discussed with them either during an additional phone call or during home visit. Previous studies have shown that treatment of osteoporosis with TPTD or other anabolic agents is more expensive than treatment with alendronate or risedronate [26, 27]. To the best of our knowledge, the cost-effectiveness of patient support programs for improving persistence with TPTD has not been published previously.…”
Section: Discussionmentioning
confidence: 99%